Determinasi Perilaku Keuangan Mahasiswa Generasi Z: Peran Hedonisme, Self-Efficacy, dan Locus of Control - Naiola, Fransiscus; Olivia Latumahina (Journal Financial, Business and Economics, 2025)
This study aims to analyze the influence of hedonistic lifestyle, financial self-efficacy, and locus of control on students' financial management. A hedonistic lifestyle reflects an individual's tendency to seek instant gratification, while financial self-efficacy refers to one's belief in their ability to manage finances, and locus of control relates to an individual's perception of control over their life, including financial matters. This research employs a quantitative method with data collected through questionnaires distributed to accounting students at Politeknik Negeri Kupang. The sampling technique used was purposive sampling, and the data were analyzed using multiple linear regression. The results show that the hedonistic lifestyle does not significantly affect students' financial management, while financial self-efficacy and locus of control have significant effects. Simultaneously, the three variables influence students' financial management. These findings highlight the importance of strengthening psychological aspects in shaping students' wiser financial behavior.